Bacterioplankton Growth on Fractions of Dissolved Organic Carbon of Different Molecular Weights from Humic and Clear Waters - Tranvik, Lars J. (1990)
The ability of fractions of dissolved organic carbon (DOC) of different molecular weights (MW) to support bacterial growth was studied in batch culture experiments. Natural pelagic bacteria were inoculated into particle-free (0.2-μm filtered) water, taken from 10 oligotrophic lakes of differing humic content, and either used without further treatments or ultrafiltered to remove DOC of >10,000 MW or >1,000 MW. Stationaryphase abundance of bacteria in the cultures was used as an estimate of bacterial carrying capacity. High-MW DOC (>10,000) comprised an increasing fraction of total DOC with increasing total DOC and humic content of the lakes. High-MW DOC was generally more available to bacteria (i.e., more bacteria were produced per unit of organic carbon initially present) than low-MW (<10,000) DOC. The availability to bacteria of this high-MW DOC decreased with increasing humic content. However, although less available in humic lakes than in clearwater lakes, the higher abundance of high-MW DOC made it quantitatively more important as a bacterial substrate; i.e., a larger fraction of the total bacterial yield of the cultures was due to high-MW DOC compounds in humic lakes than in clearwater lakes. On the average, 48% of bacterial growth occurred at the expense of DOC of <10,000 MW. DOC of <1,000 MW was responsible for an average of 22% of bacterial growth, with no significant correlation to humic content and DOC concentration of lakes. The DOC which supports bacterial growth, as well as the total DOC, is of different quality in humic and clearwater lakes.